Preliminary Study of Caridina kaili Domestication, Endemic Shrimp to Lake Lindu, Central Sulawesi, Indonesia - Muh Herjayanto; Samliok Ndobe; Abdillah Abdillah; Muamar Muamar; Puput Melaty; Abdul Gani; Muhammad Fadli; Novian Suhendra; Abd Waris; Musdalifa Musdalifa (Jurnal Perikanan dan Kelautan, 2019)
Caridina kaili is one of the endemic shrimp in Lake Lindu, Central Sulawesi, Indonesia. This shrimp has beautiful color and potential as ornamental shrimp, so it needs to be domesticated. The successful ex situ breeding of C. kaili is also expected to avoid overexploitation the shrimp in their habitat in the future. The aim of this study to analized habitat characteristics, survival during and rearing after transportation, percentage of moulting and growth of C. kaili during post-transport rearing. Shrimp are collected in two inlet rivers in Lake Lindu, Uwe Pada and Uwe Lembosa. Transportation using a closed system with a density of 15 ind./L. Shrimp from Uwe Pada are transported for 8 hours 8 minutes, while shrimp from Uwe Lembosa 11 hours 39 minutes. The results showed that C. kaili lives in the shore of streams which have slow current and clear, substrate is coarse sand, mud-sand and leaf litter, and plant roots. The habitat has a temperature range of 18.9-22.7°C; pH 7.73-8.17 and dissolved oxygen 1.99-2.11 mg/L. Survival and percentage molting during transport ranges from 96-100% and 4-5%. During post-transportation rearing, the final survival of shrimp from Uwe Pada is higher (88%) compared to Uwe Lembosa (67%). Higher moulting percentage of shrimp from Uwe Lembosa (27.6-31.4%) and lower growth (0.31 cm long and 0.56 g weight) compared to shrimp from Uwe Pada (moulting 19.6-22.2%, 0.56 cm long and 0.81 g weight), indicate stress conditions of shrimp from Uwe Lembosa due to longer transportation. This study is the first report on the performance of C. kaili during transportation and rearing post-transportation in a controlled environment